Pengembangan Aplikasi E-Learning Dengan Menerapkan Metode Gamification - Irwan Suprianto; Fajar Pradana; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Online learning platform, also known as e-learning is a very popular media for education these days. the lack of interest from the students to the media used by the school are the main cause for the ineffective of the e-learning. interest and student satisfaction are influenced by some factor such as the feature and content does not help the student finishes their assignment so they decided not to use the application again. in order to combat these problems, a new e-learning app are developed implementing game method for the feature and content. This method are called Gamification. interest is the main target for gamification